2023
DOI: 10.1002/aenm.202301218
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Potassium Citrate to Improve the Performance of Tin‐Lead Perovskite Solar Cells

Abstract: Easy‐to‐form tin vacancies at the buried interface of tin‐lead perovskites hinder the performance of low‐bandgap perovskite solar cells (PSCs). Here, a synergistic strategy by incorporating potassium citrate (PC) into the poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) hole‐transport layer to passivate the buried interface of Sn‐Pb PSCs is reported. PC neutralizes the acidity of PEDOT:PSS and stabilizes the perovskite front surface, enhancing device stability. Citrate moieties coordinate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Moreover, after S-PASP treatment, the Sn 3d 3/2 (494.89 eV) and Sn 3d 5/2 (486.49 eV) peaks of the pristine SnO 2 film shifted to 494.65 and 486.23 eV, respectively. This indicates an increase in electron density around the Sn atoms and strong chemical interaction between SnO 2 and S-PASP . We performed peak fitting for the asymmetric O 1s (Figure e and Table S2) feature peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, after S-PASP treatment, the Sn 3d 3/2 (494.89 eV) and Sn 3d 5/2 (486.49 eV) peaks of the pristine SnO 2 film shifted to 494.65 and 486.23 eV, respectively. This indicates an increase in electron density around the Sn atoms and strong chemical interaction between SnO 2 and S-PASP . We performed peak fitting for the asymmetric O 1s (Figure e and Table S2) feature peaks.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates an increase in electron density around the Sn atoms and strong chemical interaction between SnO 2 and S-PASP. 27 We performed peak fitting for the asymmetric O 1s (Figure 2e and Table S2) feature peaks. The proportion of adsorbed oxygen in SnO 2 is 36.86%, and the proportion of lattice oxygen is 63.14%.…”
Section: Chemical Interaction Between Sno 2 Nanoparticles and S-paspmentioning
confidence: 99%
“…It was found that incorporating potassium citrate, a weak base, into the PEDOT:PSS can not only neutralize the acidity of PEDOT:PSS but also improve the quality of the perovskites thanks to the coordination of citrate anion with the Sn(II) centers and the potassium cation enhanced film crystallinity. 382 The resultant mixed Sn−Pb PSCs show a PCE of up to 22.7% with a V OC value of 0.894 V, together with improved stability.…”
Section: Buried Surfacementioning
confidence: 97%
“…Metal halide perovskite solar cells (PSCs) have attracted much attention due to their unique photoelectric properties and power conversion efficiency (PCE), from the initial 3.8% to the certified 26.1%, 1 which is close to monocrystalline silicon solar cells. This is attributed to the small exciton binding energy and long carrier diffusion length of perovskite materials.…”
Section: Introductionmentioning
confidence: 99%